2004
DOI: 10.1002/srin.200405815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre‐Processing on Thixoformability of Steel Grade 100Cr6

Abstract: Thixoforming is a new manufacturing technology which has been widely investigated for aluminium alloys. The thixoformability of steel and especially the impact of different pre-processing is subject of this paper. For the thixoforming process it is of special interest to obtain the required fraction liquid content between 20 and 40 %, a globulitic microstructure and low process temperatures. Therefore, steel primary material from three different processing routes was compared. The primary materials are rolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There has been interest in whether steel can be thixoformed in the standard state in which it is received from a steel supplier. Bulte and Bleck [22] compared the microstructure after quenching from the semisolid state for 100Cr6 rolled bar, laboratory cast billet and laboratory cast billet with liquid core reduction. They found no significant difference and therefore suggest primary as-cast billet can be used.…”
Section: Routes To Thixoformable Starting Materialsmentioning
confidence: 99%
“…There has been interest in whether steel can be thixoformed in the standard state in which it is received from a steel supplier. Bulte and Bleck [22] compared the microstructure after quenching from the semisolid state for 100Cr6 rolled bar, laboratory cast billet and laboratory cast billet with liquid core reduction. They found no significant difference and therefore suggest primary as-cast billet can be used.…”
Section: Routes To Thixoformable Starting Materialsmentioning
confidence: 99%
“…Various researchers have demonstrated that some metals can be subjected to a direct partial melting route from their as-received state (without any special treatment) in order to obtain a thixoformable microstructure (e.g. 7075 aluminum alloys (Chayong et al, 2005), 100Cr6 (Bulte and Bleck, 2004), M2 (Omar et al, 2009) and HP9/4/30 (Omar et al, 2005)).…”
Section: Introductionmentioning
confidence: 99%
“…The recrystallization and partial melting (RAP) [5] and strain-induced melt-activated (SIMA) [6] are the more established solid state feedstock preparation routes. Recently, it was shown that tool steel X210CrW12 and M2 [7], stainless steel with a peritectic reaction [8], 100Cr6 [9] and C38 [10] could be subjected to a direct partial re-melting route, from their as-received conditions, to obtain a thixoformable microstructure. The volume fraction of solid phase and its distribution are important microstructure parameters that remain to be investigated, especially at low liquid fractions, because they crucially influence the rheological behavior [11] and therefore the flow behavior of a material during its forming [12].…”
Section: Introductionmentioning
confidence: 99%